Functional Classification of Paediatric Patients with Non-syndromic Delta-Storage Pool Deficiency - Manukjan, Georgi; Eilenberger, Julia; Andres, Oliver; Schambeck, Christian; Eber, Stefan; Schulze, Harald (Hämostaseologie, 2019)
Storage pool disease (SPD) covers a group of platelet defects in which α- and/or delta-granules are reduced or cannot be secreted adequately in response to agonists. The detection of delta-granule release defects is hampered by a lack of fast and feasible tests. We aimed to implement a flow cytometry–based kinetic mepacrine assay to better identify and subgroup childhood patients with a mild to moderate bleeding diathesis and compare our method to established laboratory tests. We analysed 50 children with suspected SPD whose initial parameters were re-assessed in a second site visit. Mepacrine uptake and release patterns were correlated with CD63 exposure, platelet ADP/ATP release and content, and the bleeding score ascertained by the ISTH-BAT. Mepacrine release was overall significantly reduced in investigated patients compared with controls. Summarizing, our time-resolved approach proved to be a quick and inexpensive tool that was additionally able to distinguish between mepacrine uptake, mepacrine release, and combined defects. Classification of patients using such a kinetic assay makes it feasible to sensitively detect frequently missed SPD and to group these patients for further analyses and clinical correlations.
Keywords: platelet granules; bleeding management; flow cytometry